Effects of Music on Attention-Deficit/Hyperactivity Disorder (ADHD) and Potential Application in Serious Video Games: Systematic Review - Marina Martin-Moratinos; Marcos Bella-Fernández; Hilario Blasco-Fontecilla (JMIR Publications, 2023)
BackgroundAttention-deficit/hyperactivity disorder (ADHD) has a considerable impact on an individual's daily life. Some difficulties with timing deficits may be associated with deficiencies in attention, reading, language skills, or executive function. Music therapy, either active (playing an instrument) or passive (listening to music) has demonstrated its efficacy in reducing symptomatology in many disorders. Video games may prove to be a useful assessment and treatment tool in compensating for the difficulties with multimodal treatment in ADHD. ObjectiveThe aim of the study is to (1) analyze the evidence that music is beneficial in reducing the symptomatology of ADHD using systematic review and (2) propose the application of music in video games following music therapy strategies. MethodsSearches were conducted in PubMed, Embase, PsycINFO, Cochrane, and gray literature (Google Scholar and WorldCat). We used the following search syntax: ((music[Title/Abstract]) or (music therapy[Title/Abstract])) and (attention deficit disorder[MeSH or thesaurus term]). ResultsOf the 70 records identified, 17 provided findings that music can be beneficial in various domains of ADHD. Active music therapy improves hemispheric synchrony, social skills, aggressivity, and impulsivity. Passive music therapy improves academic skills like arithmetic, drawing, and reading comprehension, as well as attention and disruptive behaviors. The effects depend on the music genre, tempo, or task difficulty. Music in video games was generally found to be beneficial for people with ADHD. Music improves immersion and flow while playing video games. Using rhythm may also improve timing skills and immersion in patients with ADHD. Regarding the proposed application of aspects of music to therapeutic video games for ADHD, some paradigms in timing and music therapy were considered in the proposed design of video games. ConclusionsImproving ADHD treatment through the application of music in video games is proposed. Trial RegistrationPROSPERO CRD42021288226; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=288226